Family Structures in Pennsylvania and its Effect on Delinquent Acts: A Data Analysis - Verrecchia, P.J.; Arp, Robyn (International Journal of Criminology and Sociology, 2015)
This paper examines the effect of family structure on delinquent acts. Specifically, whether living arrangement (with both parents, one parent, etc...) has any impact on the type of delinquent act (person or drug) committed. Data for over 2,700 juveniles who committed a substantiated delinquent act in Pennsylvania were examined for possible effects. Two family structure variables had a significant relationship with drug offenses (one in the negative direction), and one family structure variable was associated with person offenses. Only one non-family structure predictor variable (age) was associated with both offense types.